Playing the cards you're dealt - Johnson, Varian (Scholastic Press, 2021)
"Ten-year-old Anthony Joplin has made it to double digits! Which means he's finally old enough to play in the spades tournament every Joplin Man before him seems to have won. So while Ant's friends are stressing about fifth grade homework and girls, Ant only has one thing on his mind: how he'll measure up to his father's expectations at the card table. Then Ant's best friend gets grounded, and he's forced to find another spades partner. And Shirley, the new girl in his class, isn't exactly who he has in mind. She talks a whole lot of trash- way more than his old partner. Plus, he's not sure that his father wants him playing with a girl. But she's smart and tough and pretty, and knows every card trick in the book. So Ant decides to join forces with Shirley--and keep his plans a secret. Only it turns out secrets are another Joplin Man tradition. And his father is hiding one so big it may tear their family apart... "--Dust jacket.